Методологія визначення натягів бандажних кілець турбогенераторів середньої потужності - Третяк, Олексій Володимирович; Кравченко, Станіслав Сергійович; Богожавець, Олег Миколайович; Назаренко, Вячеслав Вікторович; Жуков, Антон Юрійович (Національний технічний університет "Харківський політехнічний інститут", 2023)
Представлена робота присвячена методології визначення натягів бандажних кілець методом розрахунку напружень в деталях бандажного вузла ротора. Були проведені: статичний розрахунок центруючого кільця у стані спокою, статичний розрахунок центруючого кільця при номінальній частоті обертання та статичний розрахунок центруючого кільця при угонній частоти обертання. Ці розрахунки вперше були виконані в тривимірній постановці за методом математичного моделювання.

The presented work is devoted to the methodology of determining the tension of the banding rings by the method of calculating the stresses in the details of the banding assembly of the rotor. Taking into account the load from the action of centrifugal forces on the part of the copper coils, thermal loads and landing of the banding ring, the data for the calculation were determined. After that, the static calculation of the centering ring at rest, the static calculation of the centering ring at the nominal rotation frequency and the static calculation of the centering ring at the stolen rotation frequency were carried out. These calculations were performed for the first time in a three-dimensional setting using the method of mathematical modeling. The maximum stresses arising in the centering ring at rest and having a local character were determined. It was also determined that for all modes the stress did not exceed the permissible value.
Methodology for determining the tension of banding rings of medium-power turbogenerators
Keywords: ротор; бандажні кільця; напруження; тривимірна постановка; rotor; tire rings; tension; three-dimensional setting